Jim's journal: the diary of James Butler: a critical edition - Garner, Jane Mary (Rhodes University, Faculty of Humanities, Department of History, 1984)
From Introduction: On 17 October 1876 a young man called James Butler embarked at Poplar Docks, London on the steamer Dunrobin Castle for distant Cape Town. His destination was Grahamstown in the Eastern Province of the Cape Colony, his purpose: to recover from a severe illness, probably tuberculosis, in a warm and sunny climate. He was twenty-two years and three months old. His sheltered Quaker background had not prepared him for life in a country strange in so many ways, much less for an experience which was to change the course of his life. His visit to South Africa lasted two and a half years: at the end of it his health was largely restored and he had decided that he might return to Cradock if the doctors in London thought it advisable. Cradock was the small Eastern Cape town where in fact he was to spend the rest of his life. The diary which he kept for that crucial two and a half years begins with the voyage to Cape Town and chronicles not only his travels around the Eastern Cape, but provides also a record of his own emotional growth from a somewhat insecure boy to an assured young man confident in his own future under God's guidance.
Keywords: Butler, James, 1854-1923 -- Diaries; Quakers -- Biography